BIONOMICS OF HYALOMMA TICKS IN THREE DISTRICTS OF PUNJAB, PAKISTAN - A. Z. Durrani.; A.R. Shakoori; N. Kamal (Journal of Animal and Plant Sciences, 2008)
A survey of ticks as the vector in transmission of the disease was carried out in Rawalpindi, Multan and Lahore Districts by collecting 300 specimen of ectoparasites randomly from cattle in each district. The results showed highest prevalence (66.7%) of ticks in district Lahore while highest prevalence of lice (36.3%) and mange mites (4%) in district Rawalpindi and district Multan, respectively. The highest prevalence (12%) of Hyalomma ticks and lowest prevalence (3.1%) of Rhipicephalus was recorded in cattle. The bionomical study showed that the highest mean pre oviposition period was during spring while it was lowest in autumn .The mean oviposition period was also highest in spring . The incubation period of the ova of Hyalomma varied in different seasons. No oviposition was recorded at the temperature 100C and 85% humidity. The maximum number of eggs was laid at 340C and lowest egg production occurred at 150C. The maximum number of eggs hatched at 320C and 85% humidity. The specie wise prevalence of Theileria in the gut of ticks was confirmed by PCR test which showed highest prevalence (86.6%) for Hyalomma a. anatolicum while it was lowest (20.8%) for Hyalomma m.marginatum.
Keywords: Hyalomma a. anatolicum; Hyalomma m. marginatum; Theileria; bionomics; Punjab; Pakistan